Education Policy Formation for School Improvement Practices at Lower Secondary Level in Hanoi, Vietnam - New Quality Issue after the Law on Residence in 2006 - Kusakabe, Tatsuya (VNU Journal of Science: Social Sciences and Humanities; Vol 32 No 1S, 2016)
This study investigates the Vietnam government and Hanoi local governing body’s efforts to improve lower secondary education after the law on Residence in 2006. The law on Residence adopted by the National Assembly of Vietnam in 2006 ensures the freedom of temporary residence and relaxes the rule for shifting to permanent registration. The enforcement of the law in 2007 made Hanoi population increase from 3,751,000 (2000) to 5,276,000 (2015) and caused a bloated lower secondary education. The researcher conducted the field research twice in both central and rural areas of Hanoi from December 13, 2013 to December 25, 2013 and from December 27, 2014 to January 2, 2015. The research data were obtained from interviews and documents collected from teachers, city education officers and other researchers. The research outcome shows three points. First, improvement policies rely on teacher competition and community donation due to lack of budget in the public sector. The policies are enforced in both central and rural areas. Second, the children of migrants to Hanoi were refused from top level public schools in central Hanoi despite of the improvement policies. Moreover, rich households were sending their children to expensive private English medium schools which had recently been established. Third, the improvement policies, on the one hand, gave a better impact on the quality of education in top level schools in central Hanoi; but on the other hand, they lost their substance in rural Hanoi.